Power, faith, and fantasy : America in the Middle East ,1776 to the present - Oren, Michael B. (NewYork, 2007)
This best-selling history is the first fully comprehensive history of America$1 (Bs involvement in the Middle East from George Washington to George W. Bush. As Niall Ferguson writes, (3z(BIf you think America$1 (Bs entanglement in the Middle East began with Roosevelt and Truman, Michael Oren$1 (Bs deeply researched and brilliantly written history will be a revelation to you, as it was to me. With its cast of fascinating characters$1 (Bearnest missionaries, maverick converts, wide-eyed tourists, and even a nineteenth-century George Bush$1 (BPower, Faith, and Fantasy is not only a terrific read, it is also proof that you don$1 (Bt really understand an issue until you know its history.(3ys
Keywords: Middle East - Foreign relations - United States